Reduced Radial Peripapillary Capillary in Pathological Myopia Is Correlated With Visual Acuity - Ye, Jie; Lin, Jue; Shen, Meixiao; Chen, Wen; Zhang, Riyan; Lu, Fan; Shao, Yilei (Frontiers in Neuroscience, 2022)
Purpose: To quantify the radial peripapillary capillary (RPC) density and the peripapillary retinal nerve fiber layer (pRNFL) thickness in pathological myopia and examine associations among these factors and best-corrected visual acuity (BCVA). Methods: The cohort was composed of 41 eyes as control and 79 eyes with high myopia (59 simple high myopia; 20 pathological myopia). Optical coherence tomography angiography was done to obtain RPC density and pRNFL thickness, superficial retinal capillary plexus (SRCP) and deep retinal capillary plexus (DRCP) density. The axial length (AL) was measured. Correlations among BCVA, RPC density, pRNFL thickness, AL and other parameters were determined. Results: For pathological myopia, the densities of RPC, SRCP and DRCP were significantly less than control and simple high myopia groups (P ≤ 0.005). There was no statistical difference in pRNFL thickness between pathological myopia and simple high myopia (P = 0.063), while significant difference in global pRNFL thickness between pathological myopia and control (P = 0.008). The global RPC density showed the greatest area under the curve (AUC, AUC = 0.962, sensitivity = 94.74%, specificity = 90.00%, cutoff value = 47.8%) for pathological myopia, while the AUC of pRNFL thickness, SRCP and DRCP were only 0.675, 0.824 and 0.865, respectively. The univariate and multiple linear regression models showed that both RPC density, SRCP density and AL were correlated with BCVA (All P < 0.05). In the final BCVA model with multiple generalized estimating equations analysis, AL, RPC density and interaction between RPC and AL were shown (All P < 0.03). For an eye with AL ≥ 27.94 mm, global RPC density was predicted to be less than 48.77% with a high risk of visual impairment. Conclusions: Peripapillary alterations, both the decreasing RPC density and pRNFL thickness, occurred in pathological myopia compared to the control. The RPC density was associated with BCVA, and this relationship was affected by axial length.